Analysis of The Influence of Financial Literacy Digitalization, Digital Word of Mouth, Digital Marketing and Brand Image on Z's Generation Saving Intention in Sharia Banking - Rini Hadiyati; Budi Harto; Dhiana Ekowati; Jefriyanto Jefriyanto; Sonny Santosa (Institut Riset dan Publikasi Indonesia, 2023)
This study aims to ascertain the ways in which Generation Z's interest in Sharia banking is influenced by digital marketing, word-of-mouth, brand image, and financial literacy. Students were the research population used in this study. Purposive sampling and non-probability sampling, totaling 400, were the methods used in this study's sample strategy. By distributing questionnaires, this study employed a quantitative methodology. Using SPSS version 23.0, the acquired data was examined for data quality. Next, statistical data will be analyzed using the Partial Least Square (PLS) variance-based structural equation model. The findings of this study indicate that The interest of Generation Z in Sharia banking is influenced by financial literacy. The findings of this study indicate that interest in Sharia banking among Generation Z is influenced by digital marketing. According to the study's findings, Generation Z's interest in Sharia banking is influenced by brand perception. Based on the research findings, Generation Z's interest in Sharia banking is influenced by word of mouth.